EU vs. China: battle for trade and investments within a small open economy - Bugarčić, Filip Ž.; Filipović, Sanja; Zakić, Katarina (Business, Management and Economics Engineering, 2026)
Purpose – Small open economies face various economic challenges that require different institutional solutions. This study presents a quantitative analysis of data collected through a Delphi survey, examining the current state and potential trends in Serbia’s relations with the EU and China. The research offers insights into how a small economy, such as Serbia, might strategically plan its development by implementing experts’ opinions.Research methodology – Delphi analysis was employed as the primary methodological tool. It provided experts’ opinions about Serbia’s position vis-à-vis the EU and China regarding foreign direct investments and trade flows.Findings – Experts believe Serbia will maintain cooperation with both the EU and China but are more optimistic related to economic relations with China. While the EU remains an important partner, stronger economic ties with China are unlikely to diminish the EU’s role.Research limitations – Conducting the Delphi survey online introduced constraints, namely differences between online and in-person opinions, a limited number of questions given to experts, time restrictions, and the scarcity of publicly available data for expert analysis.Practical implications – Survey findings could be used by relevant Government bodies and institutions to formulate policies or scenarios for emergency situations. Originality/Value – This type of survey was not conducted in Serbia before, nor were there other relevant papers that could be used to compare the results, which testifies to its originality.